2020
DOI: 10.1177/0956797620929634
|View full text |Cite
|
Sign up to set email alerts
|

Cheaters, Liars, or Both? A New Classification of Dishonesty Profiles

Abstract: Experimental studies of dishonesty usually rely on population-level analyses, which compare the distribution of claimed rewards in an unsupervised, self-administered lottery (e.g., tossing a coin) with the expected lottery statistics (e.g., 50/50 chance of winning). Here, we provide a paradigm that measures dishonesty at the individual level and identifies new dishonesty profiles with specific theoretical interpretations. We found that among dishonest participants, (a) some did not bother implementing the lott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…In addition, Shalvi et al (2011) found that when people were allowed to repeat a task more than once but only the first result was valid for reporting purposes, the highest outcome was sometimes reported (even if it was not the first one). Pascual-Ezama et al (2020) found some additional profiles. In addition to the liars, they found cheater non-liars and radicals.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Shalvi et al (2011) found that when people were allowed to repeat a task more than once but only the first result was valid for reporting purposes, the highest outcome was sometimes reported (even if it was not the first one). Pascual-Ezama et al (2020) found some additional profiles. In addition to the liars, they found cheater non-liars and radicals.…”
Section: Introductionmentioning
confidence: 94%
“…The first part of the experiment consisted of an adaptation of the die-under-the-cup task proposed by Fischbacher and Föllmi-Heusi (2013), using the new paradigm proposed by Pascual-Ezama et al (2020). Participants were asked to roll the die in http://www.rollandflip.com or a similar website using their cell phone.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…As this behavior provided a chance for increased rewards -similar to declaring a false result -we decided that a "re-roll" would also constitute an act of fraud, regardless of participants' self-reported results. The re-roll is considered as a new measure of dishonest behavior in a recent study (Pascual-Ezama, Prelec, Muñoz, & Gil-Gómez de Liaño, 2020).…”
Section: Notes (Deviation From the Protocol)mentioning
confidence: 99%
“… 1 As an alternative task, one could also employ the version of the dice-rolling task used by Pascual-Ezama et al ( 2020 ). In their version, participants roll a die electronically on a website provided by the experimenter and are asked to enter the result on their computer.…”
mentioning
confidence: 99%